Advances in the direct electro-conversion of captured CO2 into valuable products - Langie, Kezia; Bak, Gwangsu; Lee, Ung; Lee, Dong Ki; Lee, Chan Woo; Hwang, Yun Jeong; Won, Da Hye (Royal Society of Chemistry, 2024)
The direct electrochemical conversion of captured CO2 (capt-eCO(2)R) into valuable chemicals has recently emerged as a promising carbon capture and utilisation technology that will contribute to achieving net-zero carbon emissions. Conventional electrochemical CO2 (eCO(2)R) typically uses pure CO2 gas as a reactant; thus, this system requires substantial energy and capital allocation across the entire process, from the initial CO2 capture to the post-CO2 conditioning for product separation. The capt-eCO(2)R addresses these limitations and presents a compelling economic advantage by integrating the CO2 capture and direct electro-conversion of captured CO2 in the form of carbamate and (bi)carbonate without a CO2 conditioning process. The capt-eCO(2)R is still in the early stages of development and is not as mature as the conventional eCO(2)R; thus, several challenges remain to be addressed to improve system performance. This review provides a comprehensive overview of the capt-eCO(2)R system, including various system configurations, suitable catalysts, and strategies to enhance performance within captured media. The reaction mechanisms depend on the form of captured CO2; therefore, we categorised them according to the type of CO2 absorbent. The outlook, ongoing challenges, and strategies for future development are also presented.